An unusual injury from a toothbrush: A case report - Ebenezer J; Adhikari D; Mathew G; Chacko R (Wolters Kluwer Medknow Publications, 2007)
The use of toothbrushes has significantly improved oral hygiene. However, if brushing of the teeth is not done judiciously, it could result in severe trauma to the soft tissues of the oral cavity. This is particularly true in the young age group, since children tend to be very playful while brushing their teeth. This article describes the case report of a child who sustained a penetrating injury while brushing his teeth. A detailed plan for the management of such injuries is also presented.